2010
DOI: 10.1177/0149206310377113
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analytic Choices and Judgment Calls: Implications for Theory Building and Testing, Obtained Effect Sizes, and Scholarly Impact

Abstract: The authors content analyzed 196 meta-analyses including 5,581 effect-size estimates published in Academy of Management Journal, Journal of Applied Psychology, Journal of Management, Personnel Psychology, and Strategic Management Journal from January 1982 through August 2009 to assess the presumed effects of each of 21 methodological choices and judgment calls on substantive conclusions. Results indicate that, overall, the various meta-analytic methodological choices available and judgment calls involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
261
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 256 publications
(270 citation statements)
references
References 68 publications
(83 reference statements)
8
261
0
1
Order By: Relevance
“…Some principles might need more basic theory development, whereby a grounded-theory approach could help (Wareham, Fox, & Cano Giner, 2014). Finally, meta-analytical techniques could be used to formally test meta-theoretical principles (Aguinis, Dalton, Bosco, Pierce, & Dalton, 2011).…”
Section: Conclusion: Paradox As a Meta-theory And Theorizing Toolmentioning
confidence: 99%
“…Some principles might need more basic theory development, whereby a grounded-theory approach could help (Wareham, Fox, & Cano Giner, 2014). Finally, meta-analytical techniques could be used to formally test meta-theoretical principles (Aguinis, Dalton, Bosco, Pierce, & Dalton, 2011).…”
Section: Conclusion: Paradox As a Meta-theory And Theorizing Toolmentioning
confidence: 99%
“…An important challenge faced by organizational science researchers is that measures of latent constructs are fallible (Schmidt 1992), and because they are only imperfect indicators of underlying constructs, observed relationships between constructs are usually smaller than the actual relationships. In fact, Aguinis et al (2011) conducted a review of almost 6,000 correlation coefficients reported in the Academy of Management Journal, Journal of Applied Psychology, Journal of Management, Personnel Psychology, and Strategic Management Journal from 1982 through August 2009 and found that the median absolute effect across all types of bivariate relationships is only .23. Interestingly, this value is very close to .20, which is what Lykken (1968) guessed was the expected correlation between any two not necessarily related variables in psychological research.…”
Section: Measurement Improving the Link Between Underlying Constructsmentioning
confidence: 99%
“…Leung (2007) provided an incisive analysis of scholarly impact from an international-and particularly East Asianperspective. Aguinis, Dalton, Bosco, Pierce, and Dalton (2011) assessed whether meta-analyses that focus on theory building have more impact than meta-analyses that focus on theory testing. And Molina-Azorin (2012) examined whether certain methodological approaches have more impact than others.…”
mentioning
confidence: 99%